Middle School as a Developmental Niche for Civic Engagement. Issue 3 (30th September 2015) - Guillaume, Casta; Jagers, Robert; Rivas-Drake, Deborah
Abstract: The present study investigated how school climate, school connectedness and academic efficacy beliefs inform emergent civic engagement behaviors among middle school youth of color. These associations were examined both concurrently and longitudinally using a developmentally appropriate measure of civic engagement. Data were drawn from two subsamples of a larger study of social/emotional development in middle school (cross‐sectional sample n = 324; longitudinal sample n = 232), M = 12 years old, 46 % female, 53 % male. Forty‐two percent (42.2 %) of the sample self‐identified as African American, 19.8 % as Multiracial or Mixed, 19.4 % as Latino, 11.6 % as Asian American or Pacific Islander, 11.6 % identified as Other, and 5.2 % as Native American. The study tested and found support for a latent mediation model in which more positive perceptions of school climate were positively related to school connectedness, and this in turn, was positively associated with civic engagement; school climate was also positively associated with academic‐self‐efficacy beliefs, but such beliefs did not mediate the climate‐civic engagement association. Implications for future research and practice are discussed.